A sharp double inequality for sums of powers revisited - Vito Lampret (Journal of Inequalities and Applications)
Abstract The proof of the monotonicity of the sequence n ↦ n Δ ( n ) $n\mapsto nΔ (n)$ , presented in the 2011 article “A Sharp double inequality for sums of powers” by V. Lampret, is corrected. Namely, it is demonstrated that, for S ( n ) : = ∑ k = 1 n ( k n ) n = ∑ j = 0 n ( 1 − j n ) n $S(n):=\sum _{k=1}^{n}\left (\frac{k}{n}\right )^{n}=\sum _{j=0}^{n} \left (1-\frac{j}{n}\right )^{n}$ , the sequence n ↦ n ( e e − 1 − S ( n ) ) $n\mapsto n\left (\frac{e}{e-1}-S(n)\right )$ is strictly increasing.